Penguatan Nilai Keagamaan dan Silaturahmi Masyarakat melalui Program Ngaji Bersama (Studi Kasus Masjid Toriqotul Huda Kecamatan Ngebel, Kabupaten Ponorogo) - Aliuswatur Rukhama; Rifqi Humaida (Social Science Academic, 2025)
This community service program aimed to strengthen religious values and foster fellowship among congregants through a communal Qur’an study at Toriqotul Huda Mosque, Ngrambing Hamlet, Sahang Village, Ngebel District, Ponorogo Regency. The program was carried out using a participatory approach involving collective Qur’an recitation, short sermons, religious discussions, and group prayers. It was conducted for four consecutive weeks on Saturday nights after the evening prayer, engaging participants across generations. The results indicated improvements in the quality of Qur’an recitation, the emergence of collective awareness to preserve religious traditions, and stronger social bonds among community members. Furthermore, the mosque administrators initiated efforts to establish the communal study as a regular agenda and to expand other religious activities.